Effect of Microgreens Blanching Process Time on Total Dietary Fiber, Antioxidant Activity, and Organoleptic - Nafisah, Donna Azhar; Resti, Nina; Kurniawati, Dewi Marfu’ah; Arfan, Mohammad; Widodo, Wahyu; Afifah, Diana Nur (Progress in Nutrition, 2025)
Background and aim: Excessive lipid accumulation is a prevalent condition that causes oxidative stress and bacterial imbalance in the intestine, leading to obesity. To reduce the prevalence, several studies have proposed the use of microgreens, such as red spinach, radish, and mustard greens, due to their high dietary fiber content. Therefore, this study aims to determine antioxidant activity, total dietary fiber, and organoleptic properties of different varieties of microgreens with and without blanching process. Methods: The study procedures were carried out using Completely Randomized Design (CRD) by applying blanching treatment on red spinach, red radish, and mustard greens microgreens with variations in time of 10, 15, and 30 seconds. IC50 antioxidant test was performed using DPHH (2,2-dhipenyl1-picryhydrazyl) method, while total dietary fiber was assessed with the enzymatic gravimetric method. Organoleptic tests were carried out using hedonic and Just About Right (JAR) assessments on 67 panelists. Subsequently, the data obtained were analyzed using the Kruskal-Wallis statistical test. Results: The results showed that the 30-second blanched mustard greens (8401.05 ppm), fresh radish (11793 ppm), and 15-second blanched red spinach (15382 ppm) had the highest IC50 antioxidant activity. Meanwhile, the 30-second blanched red spinach (7.9 g/100 g), fresh red radish (7.09 g/100 g), and 10-second blanched mustard greens (6.69 g/100 g) had the highest total dietary fiber. The results also showed that the optimal treatments were observed in 15-second blanched red spinach, fresh red radish, and 30-second blanched mustard greens. Conclusions: Blanching process affected antioxidant activity, total dietary fiber, texture, taste, and color of red spinach microgreens. The treatment was also known to influence total dietary fiber, texture, taste, color, and aftertaste of red radish microgreens. Meanwhile, in mustard greens, blanching process only affected antioxidant activity, texture, and taste.